Fluorescein as commercial and environmentally friendly inhibitor against corrosion of mild steel in molar hydrochloric acid medium. (2020) - Arrousse, N.; Mabrouk, E.; Salim, R.; Ismaily alaoui, K.; El Hajjaji, F.; Rais, Z.; Taleb, M.; Hammouti, B.
Abstract: The inhibition effect of commercial and non-toxic compound: Fluorescein (FLUO) on the corrosion of mild steel in 1 M HCl solution. The experimental part was performed using absorbance difference measurements, Potentiodynamic polarization and Electrochemical impedance spectroscopy techniques. The results indicate that the fluorescein is a smart inhibitor against corrosion in acidic medium achieving a value of 85% at low concentration of 10 −4  M. These results were confirmed by scanning electron microscopy (SEM) and Energy dispersive X-ray (EDX) analyses. The adsorption behavior this inhibitor was well modeled by various isotherms models (Al-Awady, Flory-Huggins, Temkin). The theoretical part were carried out by DFT at B3LYP/6-31G (d, p) level using Gaussian 09 program. The results obtained with experimental data are in good correlation with theoretical result.